Students' Mathematical Problem-Solving Skills in Statistics Using an E-LKPD-Assisted Problem-Based Learning Model - Adzkia Rahmatina; Ardhi Prabowo (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematical problem-solving skills are one of the key competencies that need to be developed in mathematics education because they support students in understanding problems, formulating strategies, carrying out solutions, and evaluating results systematically. However, these skills remain a challenge for students, particularly in mathematics learning involving contextual problems. This study aimed to describe students' mathematical problem-solving skills in statistics using a Problem-Based Learning (PBL) model supported by Electronic Student Worksheets (E-LKPD) based on Polya's problem-solving stages. The study employed a qualitative descriptive case study involving 32 eighth-grade students from Class VIII E at SMP Negeri 12 Semarang who participated in PBL supported by E-LKPD. Based on the mathematical problem-solving test results, three students representing the high, moderate, and low categories were purposively selected as the research subjects. Data were collected through mathematical problem-solving tests and semi-structured interviews and analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing and verification. Data credibility was strengthened through method triangulation. The results showed that students in the high category completed all four stages of Polya's problem-solving process. Students in the moderate category completed the stages of understanding the problem, devising a plan, and carrying out the plan but had difficulties in the looking-back stage. Meanwhile, students in the low category were unable to complete all four stages. These findings indicate that students' mathematical problem-solving skills differed across the three categories after participating in PBL supported by E-LKPD. The looking-back stage was the most challenging for students and therefore requires greater attention during the mathematics learning process.